100 YEARS OF INSULIN: A brief history of diabetes genetics: insights for pancreatic beta-cell development and function. Issue 3 (22nd July 2021) - Ikle, Jennifer M; Gloyn, Anna L
Abstract : Since the discovery of insulin 100 years ago, our knowledge and understanding of diabetes have grown exponentially. Specifically, with regards to the genetics underlying diabetes risk, our discoveries have paralleled developments in our understanding of the human genome and our ability to study genomics at scale; these advancements in genetics have both accompanied and led to those in diabetes treatment. This review will explore the timeline and history of gene discovery and how this has coincided with progress in the fields of genomics. Examples of genetic causes of monogenic diabetes are presented and the continuing expansion of allelic series in these genes and the challenges these now cause for diagnostic interpretation along with opportunities for patient stratification are discussed.